(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2018)
The Healthy Indonesia Program aims to improve health status through health efforts and equitable health services. The positive side of the success of health development is the increasing life expectancy. But it has a negative impact, namely the increasing incidence of degenerative diseases, one of which is hypertension. Hypertension is often called the "silent killer" because it can appear without symptoms or warning signs, so many do not realize it so that the prevalence of hypertension increases. The breadth of the work area and the lack of health workers, can lead to a lack of public access to health services, so the elderly who have hypertension are less able to control the condition of the disease. Cadres of Non-Communicable Diseases Posyandu (PTM) can be the first line in reaching the community, when health workers are not available. Posyand cadres can also be an extension of their hands in increasing people’s knowledge and understanding of hypertension, even cadres can carry out blood pressure checks independently. The purpose of community service is IbM activities for Posyandu cadres of PTM, especially in Kelurahan Bantarsari in the form of counseling about hypertension and training in blood pressure measurement. The population and sample in this service were 24 cadres in Bantarsari village. Data was collected using a questionnaire in the form of questions to find out the knowledge of participants before and after training and a checklist to measure skills. Data analysis using the Paired-Samples T Test. The material used is a blood pressure measuring device, the OMRON brand digital sphygmomanometer using a new battery. The results of this activity are all female cadres, with a age range of 21-45 years. Educational background for cadres is 79.16% of high school graduates and 20.84% ??of junior high school graduates. The results of the Paired-Samples T Test analysis obtained p value 0,000 which means that there is an influence of counseling and training conducted on cadre knowledge about blood pressure measurement. In conclusion, counseling and training for cadres has a good influence in increasing their knowledge, so it is expected to reduce the incidence of hypertension in their target areas.